The Languages of Kerala and Lakshadweep,Vol.15 - Devy,G.N; Sreenathan, M.; Koyippally, Joseph (New Delhi: Orient Blackswan, 2015)
A survey of languages of Kerala and Lakshadweep.
"The People's Linguistic Survey of India is a project of Bhasha Research and Publication centre, partly funded by Sir Jamsetji Tata Trust, Mumbai"-- Title page verso.
Includes bibliographical references (pages 265-268) and index.
Includes passages in Malayalam and other languages of Kerala with translations.
Keywords: Malayalam Language; Language surveys -- India -- Kerala; Language surveys -- India -- Lakshadweep